Dessalinização da água e seletividade iônica em membranas de grafeno kagome - Ferreira, Rhayla Mendes (2024)
Population growth in major urban centers and the high demand from industries increase the need for potable water. However, approximately 97% of the water available on our planet is found in seas and oceans. Additionally, the quantity and quality of accessible freshwater are directly affected by global warming, making the search for new techniques and materials to obtain potable water essential. This dissertation investigates the potential of Kagome graphene (KG), 2-triangulene, and 3-triangulene membranes in desalination processes and ion selectivity. Molecular dynamics (MD) simulations with KG membranes in saline solutions (0.5 M and 1.0 M) and uniform electric fields ranging from 0 to 0.5263 V ·nm−1 were conducted to assess system viability. It was observed that the 2-triangulene membrane allowed the natural passage of water molecules but retained ions in the absence of an electric field, indicating promising behavior for desalination processes. Below 0.0877 V ·nm−1, 2-triangulene exhibited greater selectivity for Na+, while above 0.0877 V ·nm−1, it retained more ions than the 3-triangulene membrane, even at higher salt concentrations. Both membranes displayed non-ohmic behavior. Although complete desalination was not achieved, the ion selectivity and performance of the 2-triangulene membrane open new possibilities for optimizing membrane design and adapting this technology to various industrial contexts, contributing to advances in water purification technologies.